The Silima-Lima Waterfall’s Potential as Halal Tourism: A SWOT Analysis - Napitupulu, Rodame Monitorir; Lubis, Delima Sari; Silitonga, Juliansyah (Universitas Islam Negeri Sunan Kudus, 2022)
This study aims to determine the strengths of the halal tourism potential of Silima-lima Waterfall, to find out the weaknesses of the halal tourism potential of Silima-lima Waterfall, to find out the opportunities possessed by the halal tourism potential of Silima-lima Waterfall, to find out the threat that is owned by the halal tourism potential of Silima-lima Waterfall. This research is descriptive qualitative research, the analytical method used is the SWOT analysis technique. Data collection techniques used are observation, in-depth interviews, and documentation, the validity of the data used is member check. Based on the results of the study, it is known that Silima-lima Waterfall tourism has some strengths in the form of uniqueness and beauty of the waterfall, the weakness of Silima-lima Waterfall is that many facilities in the jogging track area are damaged, especially the guardrail, of course, this will endanger tourists. The Silima-lima Waterfall has the opportunity to become a pioneer as a halal tourist destination in the South of Tapanuli Regency. Unfortunately, Silima-lima Waterfall also has a threat in the form of a lack of public understanding about halal tourism, lack of readiness of human resources to support the realization of halal tourist destinations.